The impact of government purchase price policy of rice for producers and consumers in Indonesia - Tri Wahyudi Saleh; Benyamin Lakitan; Dedik Budianta; Muhammad Yamin; Gemala Cahya; Muhammad Huanza (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2024)
One of the rice policies was the government purchase price policy which was the price in grain or rice purchases by the Government at producer level to be stable become government rice reserves. The point of this research was to define the impact of the government purchase price policy of rice for producers and consumers. This research was conducted using qualitative analysis with descriptives based on tabulations of secondary data. Results of the research showed that government purchase price was part of the government's efforts to protect the basic price of grain and rice at the farm level thus creating affordable input prices and providing economic added value to farmers. The study found that an improvement in government purchase price  by 18-20% could increase the price of grain and rice from March to August 2023. The total percentage change in prices from March to August 2023 for dry harvested grain was 10.3%, dry milled grain was 10.8%, premium rice was 0.6%, medium rice was 3.2% respectively. Meanwhile, the impact on consumers of this policy was the occurrence of inflation of 0.41% which caused rice prices to increase. The government should evaluate the Government Purchasing Price (GPP) gradually every year.